Co-designing ACP service delivery with consumers in New Zealand. Issue 2 (1st June 2012) - Manson, L.; Snow, B.
Abstract : Auckland District Health Board together with the New Zealand ACP Cooperative held co-design workshops with consumers to explore how consumers want ACP services delivered. The questions and topic areas covered included (1) who should be involved; (2) what do you want to plan for; (3) when should these discussions take place; (4) where should ACP be done; and (5) how should ACP be done? The key themes - the ACP process should be owned first and foremost by the patient and that medical and end of life care experts should be a resource for families to draw upon as advisors and enablers of the ACP process, not the owners or drivers of it. ACP conversations need to be normalised and should take place in people's homes or in community settings. For many people living is hard enough (i.e. making ends meet) let alone planning for death. The practical aspects of living and dying took precedence– not medical care and treatment decisions. To successfully roll-out ACP to the general population, its delivery needs to be owned by the community and consumer groups. As a result of these workshops, alternative models of ACP delivery are being explored including public awareness, education, public debate, cross-sector collaboration and the use of humour. ACP has largely developed out of medical need for informed decision-making to address the changing dynamics of dying. These workshops suggest that it may have evolved differently if it grew out of the consumer's end-of-life planning needs.